Chapter 4 The municipal assembly as a scene of local democracy and subaltern political experiences in Finland, 1865-1917 - Suodenjoki, Sami (Taylor & Francis, 2023)
Approaching subalternity from a broad Gramscian angle, this edited collection contributes to the understanding of popular politics in parliamentary, autocratic, and colonial contexts. The book explores individual stories and micro-histories of complaints, requests, rumors, and other mediated and unmediated interactions between political institutions and the subjects they claimed to govern or represent. It challenges the approaches of institutionally oriented political historiography and its attention to the top-down construction of political representation, citizenship, and power and powerlessness. The book discusses more subtle forms of agency and the spaces these pertained to, which could indicate contestation or resistance taking place within a framework of loyalty towards the existing political institutions. This research does not only bridge the divide between political and apolitical frames of reference, but it also provides a new perspective on the dichotomy between loyalty and resistance by acknowledging the nuances of these seemingly opposing stances. With case studies from Europe, North Africa, South America, and India, the chapters cover political communication in proto-democratic, democratic, imperial, and authoritarian contexts. This volume is crucial reading for undergraduates, postgraduates, and scholars in history and social sciences who are interested in political culture and the mechanisms of negotiating local, national, or imperial identities.